Analisa Terhadap Pergeseran Peran Strategis Wanita Di Era Informasi Serta Solusinya Menurut Islam - Al-Bahra bin Ladjamudin; Mukti Budiarto; Tuti Nurhaeni (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2015)
Women are the largest part of the community. If they are good, the community would be good. Conversely, if their moral (akhlaq) is damaged, they would devastate the community theirselfes. Today women are being lulled by a propaganda which called emancipation, under the pretext of elevating women or regarded as women's liberation. The cluster freedom of women try as much as possible to drag women to have an equal footing with men, women should undress their muslim clothes), women should make up as beautiful as possible, outgoing, feminine, appear attractive to men when she comes out form her house, Emancipation has destroyed joints and basic rules of community life, to sow the seeds of freedom, to make a living woman to be selfish and arrogant. Through the means of information, women are very easily exposed, even commercialized. Finally women have no hope of being a wife, mother, sister, or child of flesh. The nature of the woman turned into a bitch, and reactive violent as men. Surprisingly, the women actually like it, and feel very proud to be like men. We should acknowledge that there are very rarely woman who hates.